THE “SILENT” WAR FOR FUTURE OF THE TOURISM & TRAVEL INDUSTRY, THE COMPETITION OF THE ARTIFICIAL VERSUS THE NATURAL INTELLIGENCE - Hristova , Tefka; Stoyanova, Milena (Revista Inclusiones, 2020)
Annually, the tour industry increases its income, and with that comes up a main objective which interests everyone -the human resources problem. The competitive environment puts everyone up in front of need for actions of satisfying the primar necessitiesof the common user. All kinds of industries and economical sectors are paying attention to the IT management, which is in hyper dynamic bloom. They keep coming with innovations that to the common human nature still seem like science fiction. The automotation was the creation of the 20th century, which has transformed into daily routine to us, and the roboticization is the creation of the 21st century –artificial intelligence is already a fact. The science is exponentially developing, and now there is a visible threat in the face od the human labor.